Direct anterior composite veneers in vital and non-vital teeth: A retrospective clinical evaluation. Issue 11 (November 2015) - Coelho-de-Souza, Fábio Herrmann; Gonçalves, Daiana Silveira; Sales, Michele Peres; Erhardt, Maria Carolina Guilherme; Corrêa, Marcos Britto; Opdam, Niek J.M.; Demarco, Flávio Fernando
Abstract Objectives This retrospective, longitudinal clinical study investigated the performance of direct veneers using different composites (microfilled × universal) in vital or non-vital anterior teeth. Methods Records from 86 patients were retrieved from a Dental School clinic, comprising 196 direct veneers to be evaluated. The FDI criteria were used to assess the clinical evaluation. The survival analysis was done using Kaplan–Meier method and Log–Rank test. The multivariate Cox regression with shared frailty was used to investigate the factors associated with failure. Results A total of 196 veneers were evaluated, with 39 failures. The mean time of service for the veneers was 3.5 years, with a general survival rate of 80.1%. In the qualitative evaluation of the restorations, microfilled composite showed slighty better esthetics. The annual failure rates (AFR) were 4.9% for veneers in vital teeth and 9.8% for non-vital teeth with statistical significance (p = 0.009). For microfilled and universal veneers the respective AFRs were 6.0% and 6.2% (p > 0.05). Veneers made in non-vital teeth had a higher risk of failure over time compared to those made in vital teeth (HR 2.78; 95% CI 1.02–7.56), but the type of material was not a significant factor (p = 0.991). The main reason for failure was fracture of the veneer. Conclusion Direct composite veneers showed a satisfactory clinical performance. Veneers performed in vital teeth showed a better performance than those placed in non-vital teeth. No difference in the survival rate for different composites was found, although microfilled composites showed a slightly better esthetic appearance. Clinical significance Direct composite veneers show good results in esthetic dentistry nowadays. Composite veneers in vital teeth have a lower risk of failure than those in non-vital teeth.